Failure of response to combination therapy of adalimumab and infliximab in a recalcitrant patient of severe psoriasis and major thalassemia: A case report. Issue 3 (3rd February 2020) - Goldust, Mohamad; Rahmatpour Rokni, Ghasem; Gupta, Mrinal; Lotti, Torello; Bathaei, Marzieh
Abstract: This is the first case report of combination therapy in psoriasis with underlying thalassemia that failed after months. The relation of thalassemia with severity of psoriasis and response to treatment should be evaluated in more studies. Abstract : This is the first case report of combination therapy in psoriasis with underlying thalassemia that failed after months. The relation of thalassemia with severity of psoriasis and response to treatment should be evaluated in more studies.